Professionalism, emotional wellbeing, and dropout intention in health professions students during the pandemic - Jesus M. Castagnetto; Dante E. Hancco-Monrroy; Luz M. Caballero-Apaza; Denices Abarca-Fernández; Fany A. Condori-Cardoza; Raul de Lama-Morán; Jose R. Carhuancho-Aguilar; Sandra Gutiérrez; Martha H. Gonzales Sota; Nancy Berduzco-Torres; Roberto C. Delgado Bolton; Luis Vivanco (Scientific Data)
Abstract In March 2020, the WHO declared the start of the COVID-19 pandemic. Peru was among the most affected countries, and one of the first ones to impose a strict lockdown. As a consequence, Peruvian universities were forced to change their classes from an in-person to a remote methodology during the academic year 2020–21. During this period, a cross-sectional online survey-based study was performed in medical and nursing faculties from four Peruvian universities (two of them public). The study sample, composed by 1707 undergraduate students (441 males) attending classes from home, answered three scales for measuring specific elements of professionalism (clinical empathy, teamwork, and lifelong learning abilities) in medicine and nursing, and four scales for measuring loneliness, anxiety, depression, and subjective wellbeing. In addition, 15 demographic, epidemiological, and academic variables (including dropout intention) were also collected. All this information is presented in a dataset that is available to other researchers and medical and nursing educators. Information concerning the data records, technical validation, and usage notes are also reported.